2021
DOI: 10.3390/membranes11040234
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Downregulates the CaV1.2 L-Type Ca2+ Channel via Gi/cAMP/PKA/CREB Signaling Pathway in Cardiomyocytes

Abstract: Oxytocin (OT) and its receptor (OTR) are expressed in the heart and are involved in the physiological cardiovascular functional system. Although it is known that OT/OTR signaling is cardioprotective by reducing the inflammatory response and improving cardiovascular function, the role of OT in the cardiac electrical excitation modulation has not been clarified. This study investigates the molecular mechanism of the action of OT on cardiomyocyte membrane excitation focusing on the L-type Ca2+ channel. Our method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…As OTR belongs to the G protein-coupled receptor superfamily, the long-term OT treatment could activate Gαi proteins of OTR and inhibit AC1 activity [ 58 ]. However, the activation of the AC1/PKA/pCREB pathway in acute and chronic pain induces postsynaptic LTP to enhance synaptic transmission efficiency, thus resulting in central sensitization [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As OTR belongs to the G protein-coupled receptor superfamily, the long-term OT treatment could activate Gαi proteins of OTR and inhibit AC1 activity [ 58 ]. However, the activation of the AC1/PKA/pCREB pathway in acute and chronic pain induces postsynaptic LTP to enhance synaptic transmission efficiency, thus resulting in central sensitization [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have reported that OT may activate gamma-aminobutyric acid (GABA)ergic interneurons in the spinal dorsal horn and promote GABA release to inhibit the function of postsynaptic glutamate receptors, including NMDA receptors [ 52 , 61 ]. A recent study has demonstrated that long-term treatment with OT can downregulate the expression of PKA and pCREB in neonatal cardiomyocytes [ 58 ]. Comparison of the different mechanisms mentioned above implies that the effect of long-term treatment with OT may be different from the short-term or single-dose reatment.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal rat cardiomyocytes were prepared as described previously [ 10 , 11 ]. Neonatal ventricular myocytes were prepared from 2-8-days-old Wistar rats and maintained at 37 °C under 5% CO 2 in Dulbecco’s modified Eagle’s medium (DMEM) that was supplemented with 10% fetal bovine serum for 24 h, followed by an additional 24 h incubation in DMEM with or without protein kinase inhibitor, or a protein kinase activator (see the figure insets).…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments confirmed to the Guidelines for the Care and Use of Animals at Oita University, and the NIH guidelines were approved by the institutional committee. Neonatal rat cardiomyocytes were enzymatically isolated and cultured as previously described [ 37 , 38 , 39 ]. After 24 h of culture, >70% of the cells adhered to the substrates and started to exhibit spontaneous beating.…”
Section: Methodsmentioning
confidence: 99%